2015
DOI: 10.5937/pramed1503055m
|View full text |Cite
|
Sign up to set email alerts
|

Influence of kinesiophobia on activities of daily living of elder institutionalized persons with chronic pain

Abstract: Aging of population leads to limitations in functional abilities and in activities of daily living (ADL) which are the essential elements of independent care of oneself. Limitations in performing these activities result in increasing need for assistance and institutionalizing of the elderly. The aim of this study was to investigate the influence of fear of movement, or kinesiophobia, on ADL in elder institutionalized people with chronic pain. The research included 60 individuals older than 65 suffering from ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 11 publications
1
15
1
Order By: Relevance
“…However, both groups demonstrated TUG outcomes below the required threshold at that time. These findings are in accordance with previous studies in which a relation was demonstrated between kinesiophobia and the willingness or ability to perform transitions during activities of daily living [47,48]. Based on the proposed findings, one can conclude that a high level of kinesiophobia at time of discharge may negatively affect the short-term performance of the TUG test in patients with knee replacement.…”
Section: Discussionsupporting
confidence: 92%
“…However, both groups demonstrated TUG outcomes below the required threshold at that time. These findings are in accordance with previous studies in which a relation was demonstrated between kinesiophobia and the willingness or ability to perform transitions during activities of daily living [47,48]. Based on the proposed findings, one can conclude that a high level of kinesiophobia at time of discharge may negatively affect the short-term performance of the TUG test in patients with knee replacement.…”
Section: Discussionsupporting
confidence: 92%
“…Our study is in agreement with Milenković M.et al whose research indicates that kinesiophobia occurred in a considerable number of participants (more than a half) in a sample of elder institutionalized population with chronic pain. [3] Researches conducted by Crombez G et al, [11] Vlaeyen JW et al [12] and Roelofs J et al [13] state that kinesiophobia is not only an essential factor resulting in the avoidance of movement, but also the factor leading to disability even more than the pain itself.…”
Section: Discussionmentioning
confidence: 99%
“…Hence aging may lead to limitations in functional abilities and in activities of daily living. [3] Statistics show that pain is a critical public health problem affecting 37-41% people worldwide. The persistence of pain can lead to changes in behaviour for both physical and psychological reasons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations